Microevolution Processes in Fieri Population as Estimated by Isonymy Techniques - Turku, Silvana; Basha, Hyrida; Mikerezi, Ilia (Richtmann Publishing, 2012)
The genetic structure of Fieri population was analyzed through the distribution of surnames obtained by a sample of3’471 marriages registered in the period 1946-2006. The data were recorded for every five years starting from 1946 (than 1951,1956 and so on) to 2006. Estimations of Fisher’s 􀄮, an indicator of richness of surnames, and 􀈞 of Karlin-McGregor, indicator ofmigration rates, were obtained for both natives and immigrants. These indicators showed higher values in immigrants. The samewas demonstrated even by log2k-log2S regression line. Two different estimations of relationships between all possiblecombinations of cohorts born in nine different decades were obtained through Euclidean distance and Lasker’s coefficient ofrelationship, respectively. Comparisons of Ft, coefficient of total inbreeding and Fisher’s 􀄮 indicated that any decrease of Ft wasfollowed by an increase of 􀄮 as the result of recent migration.